Tonga : 2010 Article IV Consultation; Staff Report, Staff Supplement, and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
Tonga's high debt and the apparent ineffectiveness of the monetary transmission mechanism constrain the authorities' ability to support growth. In the near term, the strength of the global recovery is by no means assured, and there are multiple risks that could weaken prospects in both Europe and the United States. A further rise in world commodity and food prices would also hit Tonga hard, feeding through to inflation, growth, and the current account deficit. Tonga's high public debt now poses a major risk to economic prospects.